Risk Factors for Mortality in Elderly Patients who Live in Nursing Homes: 8-year Follow-up Period - Kucukardali, Yasar; Yalcin, Arzu; Terekeci, Murat Hakan; Ozturk, Mehmet Akif; Kucukardali, Betul; Altunok, Elif Cigdem (Asian Journal of Medical Sciences, 2019)
Background: In developed countries and our country, the ratio of the elderly to the total population is increasing due to the rise in worldwide medical care spendings and the medical workforce allocated for the treatment of the acute and chronic problems of the elderly. Aims and Objectives: The number of studies based on long-term observations of the risk factors that affect the survival and mortality rates of the elderly in nursing homes is quite rare. Currently, there are no studies concerning this issue in the country. The authors carried out an eight years prospective study to determine the risk factors for mortality in a private nursing home with a capacity of 150 beds located in Istanbul. Materials and Methods: From January 2007 to March 2015, we scanned the number of medications, comorbidities, nutritional status, age, mental score, number of falls and fractures, levels of hemoglobin, albumin, creatinine, and glucose parameters related with mortality in 612 patients admitted to the nursing home. Results: The median overall survival time was 34 months. A total of 240 (39%) residents died within eight years, 44% within two years and 55% within three years. The evaluation results shothat 360 (51%) of the 612 residents, were females and the mean age was 76.49 (± 11.36) years. Hazard ratios of the related parameters that related to mortality were respectively 1,3 for age, 1,5 for BMI less than 20kg/m2, 4,2 for more than six comorbidities, 7,01 for six to nine number of medications, 5 for dependency, 0,7 for one to three episodes of infection, 0,5 for falls, 1,3 for fracture, 3,1 for mental score of less than 18, 1,9 for hemoglobin less than 12gr/dl, 4,03 for creatinine higher than 1.5 mg/dl, 2,43 for glucose greater than 126 mg/dl, 4,8 for albumin less than 3 g/dl (95% CI). Conclusion: The risk factors causing mortality are; old age, BMI less than 20, more than six comorbidities, more than six medications, dependency, one to three episodes of infection, impaired mental score less than 18, anemia, hyperglycemia, kidney failure, hypoalbuminemia at the patients who admitted to nursing homes. Early optimal monitoring of these parameters can provide a positive contribution to the survival of elderly residents in nursing homes.